Curious George flies a kite. - Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977 (Boston, Houghton Mifflin, 1958)
A little monkey needs to be rescued when he tries to fly a kite
450
Accelerated Reader AR
Keywords: Monkeys -- Fiction; Kites -- Fiction